Analysis of Acceptance Factors in the Use of the Village Financial System (Siskeudes): A TAM and TPB Approach - Sanusi Ariyanto; Azwirman Azwirman; Fadhilah Sunny (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to analyze the factors that influence the acceptance and use of the Village Financial System (Siskeudes), and to examine which theoretical approaches are most appropriate for investigating these acceptance factors. The study employs two theoretical models: the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), incorporating variables such as ease of use, attitude, perceived usefulness, intention to use, normative perceptions, and continuous learning. The novelty of this research compared to previous studies lies in the addition of the continuous learning variable. Data were collected through questionnaires distributed directly to respondents. The sample consisted of 82 users of the Siskeudes application from various village governments in Pelalawan Regency. The data were analyzed using SPSS 20, employing both T-tests and F-tests. The results show that ease of use, usefulness, intention to use, normative perception, and continuous learning have a positive influence on the use of the Siskeudes application. However, attitude was found to have no significant effect on its usage. A key limitation of this study is that the sample was limited to village governments in a single regency.